Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Let f(x)=x−4
and g(x)=−2x+4

Find g(f(2))

0

−12

8

−8


Sagot :

Answer:

8

Step-by-step explanation:

This one is similar to the other one done with graphs , the only difference is we have equations instead of graphs.

Like the other one, we want to find f(2) and whatever that equals we plug into g(x) to find g(f(2))

So first lets find f(2)

f(x) = x - 4

f(2) = 2 - 4

f(2) = -2

g(f(2)) , f(2) = -2 , g(-2)

now lets find g(-2)

g(x) = -2x + 4

g(-2) = -2(-2) + 4

multiply -2 and -2 to get 4

g(-2) = 4 + 4

add 4 and 4 to get 8

g(-2) = 8

We can conclude that g(f(2)) = 8

f(2):-

[tex]\\ \sf\longmapsto f(2)[/tex]

[tex]\\ \sf\longmapsto 2-4[/tex]

[tex]\\ \sf\longmapsto -2[/tex]

Now

[tex]\\ \sf\longmapsto g(f(2))[/tex]

[tex]\\ \sf\longmapsto g(-2)[/tex]

[tex]\\ \sf\longmapsto -2(-2)+4[/tex]

[tex]\\ \sf\longmapsto 4+4[/tex]

[tex]\\ \sf\longmapsto 8[/tex]